Interdicting layered physical and information flow networks. (3rd April 2018) - Baycik, Nail Orkun; Sharkey, Thomas C.; Rainwater, Chase E.
ABSTRACT: This article focuses on the problem of interdicting layered networks that involve a physical flow network and an information flow network. There exist dependencies between these networks since components of the physical flow network are only operational should their counterparts in the information flow network receive enough demand. This leads to a network interdiction problem over these layered networks. The objective of the defender is to send the maximum amount of flow through its physical flow network. The objective of the attacker is to interdict components within the layered networks to minimize this maximum flow. For the case where the information supply arcs are uncapacitated, we apply a novel multi-step, dual-based reformulation technique. We apply this reformulation technique to two applications in order to provide policy-driven analysis: law enforcement efforts against illegal drug trafficking networks and cyber vulnerability analysis of infrastructure and supply chain networks. The computational results prove that our reformulation technique outperforms the traditional duality-based reformulation technique by orders of magnitude. This allows us to analyze instances of realistic size.